Lithium enrichment from a simulated salt lake brine using an integrated nanofiltration-membrane distillation process. Issue 5 (October 2019) - Pramanik, Biplob Kumar; Asif, Muhammad Bilal; Kentish, Sandra; Nghiem, Long Duc; Hai, Faisal Ibney
Highlights: NF90 and NF270 membranes achieved 23 and 44% Li separation, respectively. Mg/Li ratio changed from 10 to 0.19 and 10 to 2.1 after NF90 and NF270 treatment, respectively. The separated Li following NF treatments could be enriched by MD system. Abstract: This work aimed to evaluate the enrichment of lithium (Li) from a simulated salt lake brine by using an integrated nanofiltration (NF) and membrane distillation (MD) process. Two types of NF membranes, namely NF90 and NF270, were employed to compare their performances for Li and magnesium (Mg) rejection under various operating conditions. In the presence of a competing ion ( i.e., Mg) at different concentration, Li rejection by NF90 and NF270 membrane increased, which could be attributed to ion-shielding effects. On the other hand, Li rejection by the NF membranes slightly reduced by increasing the applied pressure from 4 to 8 bar. Increasing the pH from 3 to 11 did not significantly affect Li rejection efficiency. Under optimum operating conditions, the Mg/Li molar ratio changed from 10 to 0.19 after NF90 treatment, and 10 to 2.1 after NF270 treatment. NF90 and NF270 membranes achieved 23 and 44% Li separation, respectively. The separated Li following NF treatments could be further enriched or concentrated significantly (80%) by using the direct contact-MD system. This study demonstrates that an integrated membrane process could be an efficient method for lithium recovery from salt lake brines.